Genetic variations in NLRP3 and NLRP12 genes in adult-onset patients with autoinflammatory diseases: a comparative study - Yun, Mark; Deng, Zuoming; Navetta-Modrov, Brianne; Xin, Baozhong; Yang, Jie; Nomani, Hafsa; Aroniadis, Olga; Gorevic, Peter D.; Yao, Qingping (Frontiers in Immunology, 2024)
Objectives: Cryopyrin-associated periodic syndrome or NLRP3-associated autoinflammatory disease (NLRP3-AID) and NLRP12-AID are both Mendelian disorders with autosomal dominant inheritance. Both diseases are rare, primarily reported in the pediatric population, and are thought to be phenotypically indistinguishable. We provide the largest cohort of adult-onset patients and compared these diseases and the gene variant frequency to population controls. Methods: A cohort of adult patients with AIDs were retrospectively studied. All underwent molecular testing for periodic fever syndrome gene panels after extensive and negative workups for systemic autoimmune and other related diseases. Patients were divided into Group 1-NLRP3-AID patients with NLRP3 variants (N=15), Group 2-NLRP12-AID with NLRP12 variants (N=14) and Group 3-both NLRP3 and NLRP12 (N=9) variants. Exome sequence data of two large control populations including the ARIC study were used to compare gene variant distribution and frequency. Results: All 38 patients were Caucasian with women accounting for 82%. Median age at diagnosis was 41±23 years and the disease duration at diagnosis was 14±13years. We identified statistically significant differences between the groups, notably that gastrointestinal symptoms as well as evaluations for same were significantly more frequent in patients with NLRP12 variants, and headaches/dizziness were less common among the NLRP12 patients. Livedo reticularis was noted in four patients, exclusively among NLRP12 carriers. Over 50% of patients in Groups 1 and 2 carry low-frequency disease-associated variants, while the remaining carry rare variants. We unprecedently identified digenic variants, i.e., the coexistence of NLRP3 and NLRP12, which were either both low frequency or low frequency/rare. Allele frequencies of all variants identified in our cohort were either absent or significantly lower in the control populations, further strengthening the evidence of susceptibility of these variants to SAID phenotypes. Conclusion: Our comparative study shows that both NLRP3-AID and NLRP12-AID share similar clinical phenotypes, yet there are significant differences between them with regard to gastrointestinal and neurological symptoms. A spectrum of high to low genetic variations in both genes can contribute to SAID individually or in combination.